Performa of SCARA based intelligent 3 axis robotic soft gripper for enhanced material handling. (February 2023) - Dinakaran, Venkatesa Prabu; Balasubramaniyan, Meenakshi Priya; Muthusamy, Suresh; Panchal, Hitesh
Highlights: The gripping function is accomplished by the enhanced Cosserat (EC) and improved genetic (IG) algorithms. The robotic operating system (ROS) based soft robotic gripper is mounted on a 3-axis SCARA arm to demonstrate its ability to handle a range of fragile objects. When an extra anti-slip layer is added to the inner gripper surfaces of the soft fingers, the gripper's maximum payload may be raised to 300g. Abstract: Soft robotic gripper is a model and intensively investigated area of soft robotics which is frequently motivated by nature. Human anatomical fingers are used as grippers in the current research. Robotic soft silicon grippers are constructed using hollow chambers that can be controlled by varying the pneumatic pressure inside the chambers. The soft gripper is made using casting, 3D printing, and molds. End-effectors made from flexible and soft components may frequently grasp or operate a greater variety of items with complicated geometries as compared to rigid grippers. Such grippers are an illustration of morphological computation, where mechanical compliance and material softness significantly reduce control complexity.The improved genetic (IG) and enhanced Cosserat (EC) algorithms carry out the grasping function. The actuator is made of shape memory alloy(SMA) and has configurable degrees of freedom (DoF).The proposed soft finger was prototyped using 3D printing and silica-reinforced polysiloxane cross-linked polymer, and it was then simulated using ANSYS software. The geometric advantage correlations of the prototyped finger's experimental input force against pressure and output stress, strain, and total deformation are in good agreement with the results of the simulation. The soft robotic gripper, which is based on the robotic operating system (ROS), is put on a 3-axis SCARA arm to show off its capacity to handle a variety of delicate things of different sizes and shapes, including eggs, fruits, vegetables, and glass objects. According to test results, the proposed end-effector gripper is capable of grabbing an object with a maximum weight of 401.9grams and a maximum diameter of 240mm. The suggested soft gripper's force and displacement at larger pressure are 12.5 psi, primary stiffness is 4.84 N/mm, and maximum load-bearing capacity is 36.4 N. The designed gripper model offers an improved object grasping with various curvatures of 213.65 pulling force of patterned at 35 kpa, 51.45 pulling force of non-patterned at 35 kpa, and 126.87 maximum pulling forces at 50 kpa, according to experimental validations and analysis of object grasping kinematic pulling force.During "pick and place" tasks, the versatile two-fingered robotic gripper must be able to recognize finger bending and stiffening. The humanistic grippers may substantially enhance the interaction between a gripper and exploitable materials.